'Finding' and 'discovering': How understanding researchers' search and discovery behaviour informed the building of Cambridge Core. Issue 1 (16th December 2016) - Doshi, Nisha
Abstract : Key points Researchers most often visit publisher platforms to 'find' a specific article or chapter after 'discovering' available resources elsewhere. Keywords in the title and author names are the two most important criteria for identifying relevant material. Students consider access to be an important criterion for item selection. For both humanities and social sciences (HSS) and science, technology, and medicine (STM), user behaviour when identifying relevant content is remarkably similar. Students and researchers tend to gather content for later use rather than read it in detail as soon as they find it.